STUDY ON INTERFERENCE INSTALLATION OF HYDRAULIC KEYLESS SLEEVE COUPLING FOR A SHIP’S TAIL SHAFT - ZHANG QingJu; WANG DeLun; ZHANG YuNing; WANG LiHua (Jixie qiangdu)
Absrtact Aiming at the safety problem of the hydraulic keyless sleeve coupling caused by the increase of bearing power of a ship’s CPP,studied the interference installation of coupling sleeve-cone sleeve-tail shaft for transferring torque and thrust. Firstly,analyzed the composition and working principle of hydraulic non-key sleeve coupling,then studied the thick-wall cylinder theory of the coupling interference fit,according to the formula of the stress and deformation amount at a certain diameter of the thick-wall cylinder,calculated the interference amount of coupling sleeve cone surface and axial displacement of coupling sleeve when transferring 2. 8 times rated torque. Then,calculated the tangential stress and synthesized the principal stress at the mean diameter of the sleeve-in conical surface at 2. 8 times of the rated torque,checked the strength of the coupling. Then,according to the stipulation that the maximum compressive stress of the cone surface was not more than 0. 7 times the yield strength,calculated the maximum cone surface interference and the maximum hoop sleeve axial displacement. Then,studied the influence of the installation and measurement error of the coupling on the transmission capacity. Then,considered the interference loss caused by surface roughness,selected the design values of interference and axial displacement within the allowable range of the code. Finally,studied the technical of the interference fit of the coupling. The results show that the design interference value and hoop sleeve axial displacement meets the ship inspection regulation of transferring 2. 8 times rated torque,and the cone surface compressive stress does not exceed 0. 7 times yield strength of the material,which meet the application requirements,and the research results and installation technology can be used for reference by peers.